PENGAWETAN DAGING AYAM BROILER DENGAN MEMANFAATKAN DAUN SELADA (LACTUCA SATIVA L.) DAN PENGARUHNYA TERHADAP ORGANOLEPTIK DAN TOTAL ANTIOKSIDAN: Preservation of Broiler Chicken Meat Using Lettuce Leaves (Lactuca sativa L.) and Its Effect on Organoleptic Properties and Total Antioxidant Activity - Armince Ledu; yessy Tamu Ina (Program Studi Teknologi Hasil Pertanian Universitas PGRI Banyuwangi, 2026)
This study aimed to determine the effectiveness of lettuce leaf extract (Lactuca sativa L.) as a natural preservative in improving the organoleptic quality and antioxidant activity of broiler chicken meat. The research was conducted at the Integrated Laboratory of Wira Wacana Christian University, Sumba, using a Completely Randomized Design (CRD) consisting of four levels of lettuce leaf extract concentration, namely 3%, 6%, 9%, and 12%, with four replications for each treatment. The parameters observed included moisture content, pH, organoleptic properties (color, taste, texture, and overall acceptability), and antioxidant activity measured using the DPPH radical scavenging method to determine IC₅₀ values. Data analysis was performed using ANOVA at a 5% significance level, followed by Duncan’s Multiple Range Test when significant differences were found, while sensory data were analyzed using the Kruskal–Wallis test. The results showed that the moisture content ranged from 74.41% to 75.69%, while the pH values ranged from 4.21 to 4.43, which were still within the normal range for fresh chicken meat. Sensory evaluation indicated that the 9% concentration achieved the highest scores for color, texture, and overall acceptability, whereas the 12% treatment obtained the highest score for taste. All treatments showed IC₅₀ values above 200 ppm, indicating very weak antioxidant activity. However, the 12% treatment showed the lowest IC₅₀ value of 204,826.73 ppm compared to the other treatments. In general, the addition of lettuce leaf extract has the potential to maintain sensory quality while enhancing the functional value of broiler chicken meat as a source of natural antioxidants. These results indicate that lettuce leaf extract can be utilized as a natural additive in poultry meat preservation. The presence of bioactive compounds such as phenolic compounds, flavonoids, and tannins in lettuce leaves is believed to contribute to antioxidant and antibacterial properties, which may help delay oxidative reactions and microbial growth during storage. Considering the balance between sensory quality and functional potential, a lettuce leaf extract concentration of 9% is recommended as the best treatment in this study.